ANALISIS MANAGEMENT KEUANGAN PENDIDIKAN DI SMP NEGERI 1 CIKONENG KABUPATEN CIAMIS PADA MASA PANDEMI COVID 19 - shopia, legi; hartini, titi; lisniawati, nia (Journal of Management Review, 2024)
This Education Finance Management Analyst at SMPN 1 Cikoneng describes: (1) the planning process in the preparation of the RKAS at SMPN 1 Cikoneng. (2) Implementing education financing management during the pandemic at SMPN 1 Cikoneng. (3) Examining, controlling, supervising financing carried out at SMPN 1 Cikoneng. The research method uses a qualitative descriptive approach with the aim of describing analysts regarding Education Financial Management Analysts at SMPN 1 Cikoneng. The results of this study indicate that: (1) The planning process in preparing the RKAS is carried out by a team consisting of: Principal, Treasurer, Secretary, Deputy Principal, PKS Curriculum, Student Affairs, Sapras and Public Relations, as well as Chair, Secretary, Treasurer of the Committee and represent parents. The preparation steps are in accordance with the provisions. (2) The implementation of education financing management is distributed to finance 8 education standards, during the pandemic, the financing standards experienced a significant change because they financed the purchase of health care facilities and infrastructure. (3) The auditing, controlling, and supervision of financing is carried out in accordance with applicable regulations so that targets can be achieved effectively, supervision is carried out by socializing the use of BOS funds on information boards, Monitoring and evaluation activities are carried out by the inspectorate, BPKD, the Department of Finance, The Education Office has the authority to examine the use of BOS funds. Reports are carried out at the Education Office and BPKD